Removal of Different Quantities of Straw on the Soil Surface: Effects on the Physical Attributes of the Soil and the Productivity of Sugarcane Yield in Southeast Brazil - Silva, Itallo Dirceu Costa; de Souza, Zigomar Menezes; Santos, Ana Paula Guimarães; Farhate, Camila Viana Vieira [UNESP]; de Oliveira, Ingrid Nehmi; Torres, José Luiz Rodrigues (Springer Nature, 2022)
Mechanized operations in sugarcane areas cause gradual soil compaction. On the other hand, the maintenance of straw on the soil can preserve the soil´s structural quality, increasing the productivity and longevity of sugarcane fields. Therefore, the objective of this study was to evaluate the effects of maintaining different levels of straw, on the decomposition dynamics, soil´s physical quality, Least Limiting Water Range (LLWR) and sugarcane yield under different edaphoclimatic conditions. The experiment was conducted in Iracemápolis and Quatá, São Paulo, Brazil. The experimental design was randomized blocks, with four replications. The plots were composed of 10 lines of sugarcane, with spacing of 1.5 m and 10 m in length. The sandy soil showed greater sensitivity to the maintenance of straw on the soil´s surface, where levels between 10 and 15 Mg ha−1 provide higher yield. The 0 Mg ha−1 dose reduced yield in both clayey soil (101 Mg ha−1) and sandy soil (98 Mg ha−1) during the 2013/14 crop. For the 2014/15 crop, in the sandy soil the lowest yield was achieved with the maintenance of 0 Mg ha−1 of straw on the soil´s surface (54 Mg ha−1). Regardless of the soil type, the removal of sugarcane straw does not influence the soil´s physical attributes and the LLWR, in the short term. However, higher doses of straw on the soil´s surface accelerated the rates of residue decomposition, induced by the maintenance of higher soil moisture associated with a lower temperature. So, maintaining straw levels between 10 and 15 Mg ha−1, contributed to greater productivity of sugarcane yield.
Keywords: Compaction; Mulch; Physical properties; Plant litter; Soil conservation